Calcitonin gene‐related peptide and vascular endothelial growth factor are expressed in lesional but not uninvolved skin in chronic spontaneous urticaria. Issue 8 (August 2014) - Kay, A. B.; Ying, S.; Ardelean, E.; Mlynek, A.; Kita, H.; Clark, P.; Maurer, M.
Summary Background The mechanisms for producing weals in chronic spontaneous (idiopathic) urticaria (CSU) are incompletely understood. Leucocyte infiltration with vascular leakage and expression of the potent vasoactive agents' calcitonin gene‐related peptide (CGRP) and vascular endothelial growth factor (VEGF) are features of late‐phase allergic skin reactions, previously proposed as a model of CSU. Objective To measure CGRP and VEGF expression in lesional and non‐lesional skin from CSU patients and to compare results with a control group. Methods Eight paired biopsies (one from 4–8 h spontaneous weals and one from uninvolved skin) were taken from eight patients with CSU and nine control subjects and studied by immunohistochemistry and confocal microscopy. Results Lesional skin in CSU contained significantly more CGRP+ and VEGF+ cells than non‐lesional skin. No significant differences were observed in CGRP and VEGF expression between non‐lesional skin and controls. In lesional skin, VEGF and CGRP co‐localised to UEA‐1+ blood vessels. CGRP was also expressed by neutrophils and eosinophils and to a lesser extent by CD90+ fibroblasts, mast cells, CD3+ and CD68+ cells. CGRP and VEGF expression was not related to the duration of disease. Conclusion and Clinical Relevance Increased expression of CGRP and VEGF in lesional, but not uninvolved, skin indicates that these potent vasoactive agents may play a role in wealing and tissue oedema in CSU so representing novel targets in therapy.